Topics of alternative justice and culture of peace (Revista de Investigaciones Universidad del Quindío, 2021)
The justice system in Mexico, based on the constitutional reform on human rights and access to justice provided for in Article 17 of the Constitution, has integrated into the various areas of law the mechanisms provided for in alternative justice, strengthening the administration of justice. promptly from the empowerment and legitimation of the parties in conflict, to develop the ability to resolve their conflicts and not continue with a jurisdictional process. In this sense, based on the flexibility of the process and the willingness of the parties, a citizenry is combined and encouraged that strengthens a democratic and plural society with respect, dialogue and communication. This document describes this relationship and the beneficial scope that you can continue to improve beyond the justice system.
Keywords: Democratic citizenship; alternative mechanisms; peace; plurality